Collective Dynamics in Quasi-One-Dimensional Hard Disk System - Huerta, Adrián; Bryk, Taras; Pergamenshchik, Victor M.; Trokhymchuk, Andrij (Frontiers in Physics, 2021)
We present the results of our molecular dynamic studies of collective excitations in a system of hard disks confined to a narrow quasi-one-dimensional channel. The computer simulations have been performed for the specific width of the channel in which disk arrangement resembles zigzag ordering in a vertically oriented two-dimensional (2D) triangular lattice at disk close packing. In this system which is intermediate between 1D and 2D hard disks, we found transverse excitations that obey very specific dispersion law typical of the usual optical transverse modes. This is in a sharp contrast both to the 1D case where transverse excitations are not possible, and to the 2D case where these are essentially of the shear wave nature. The peculiarities of the disk structuring and dispersion of the collective excitations in the quasi-1D hard disk system are presented and discussed for a wide range of hard disk densities.